2022
DOI: 10.25130/tjas.22.2.9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Generations and Feather Color Groups on Productive and Reproductive Performance of Female Quail

Abstract: The research was carried out in the poultry unit fields / Nineveh Research Department, to identify the effect of four generations (1st , 2nd, 3rd and 4th) and feather color groups (black, brown, desert and white) of female quail on their productive performance. The results showed a significant improvement (P <0.05) through generations from 1st to 4th on egg production percentage and weight of eggs produced / kg, a significant increase (P <0.05) for feed consumption / kg as well as a significant decrease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…According to Table (6), the number of eggs laid by the white Ukrainian quail increased significantly (P < 0.05) over the brown Ukrainian quail, which was significantly superior (P < 0.05) to the local brown quail, which was significantly superior (P < 0.05) to the local white quail during eight weeks of production. These findings were consistent with those of [9,11,24,25,26] in the presence of substantial differences in the number of eggs laid down related to the color of the plumage, it disagreed with [19] that the hue of the plumage was a significant factor in the variation in egg production. Table 6.…”
Section: Eggs Number Producedsupporting
confidence: 61%
See 3 more Smart Citations
“…According to Table (6), the number of eggs laid by the white Ukrainian quail increased significantly (P < 0.05) over the brown Ukrainian quail, which was significantly superior (P < 0.05) to the local brown quail, which was significantly superior (P < 0.05) to the local white quail during eight weeks of production. These findings were consistent with those of [9,11,24,25,26] in the presence of substantial differences in the number of eggs laid down related to the color of the plumage, it disagreed with [19] that the hue of the plumage was a significant factor in the variation in egg production. Table 6.…”
Section: Eggs Number Producedsupporting
confidence: 61%
“…But for interaction between genetic groups and plumage color we should note that the local white quail's fertility considerably decrease (P < 0.05) compared to others. The findings of [7,18,19] were supported by these results, which indicated that the hue of quail plumage had no significant impact on fertility. It did not support the findings of [8,15,16,17,20] who discovered that the color of quail plumage had a significant effect (P < 0.05) on the fertility.…”
Section: Fertility%mentioning
confidence: 67%
See 2 more Smart Citations
“…Petek et al, (2022) observed significant differences among quail breeds for HD percentage as the wild breed produced the highest HD percentage and heavier eggs than the other breeds. On the other hands, absence of any effects of quail breed on HD percentage, reported when compared four different (black, brown, desert and white) breeds of Japanese quail (Ibrahim et al, 2022).Hen-day egg production (%) results affected by adding Lcarnitine (LC) in different lines of local quail are presented in Table (3). During the overall period of experiment, the results of hen-day egg production (%) in T3 (350)mg/kg LC was significantly higher than to those fed with diets containing 0, 150 and 550 mg/kg LC, while, the non-addition of LC was the lowest rates.…”
Section: Hen Day Egg Production (Hd%)mentioning
confidence: 96%